Large resistivity change and phase transition in the antiferromagnetic semiconductors LiMnAs and LaOMnAs - Beleanu, A.; Kiss, J.; Kreiner, G.; Koehler, C.; Muechler, L.; Schnelle, W.; Burkhardt, U.; Chadov, Stanislav; Medvediev, S.; Ebke, Daniel; Felser, Claudia; Cordier, G.; et al. (Physical Review B - Condensed Matter and Materials Physics, 2013)
Antiferromagnetic semiconductors are new alternative materials for spintronic applications and spin valves. In this work, we report a detailed investigation of two antiferromagnetic semiconductors AMnAs (A=Li, LaO), which are isostructural to the well-known LiFeAs and LaOFeAs superconductors. Here we present a comparison between the structural, magnetic, and electronic properties of LiMnAs, LaOMnAs, and related materials. Interestingly, both LiMnAs and LaOMnAs show a variation in resistivity with more than five orders of magnitude, making them particularly suitable for use in future electronic devices. Neutron and x-ray diffraction measurements on LiMnAs show a magnetic phase transition corresponding to the Néel temperature of 373.8 K, and a structural transition from the tetragonal to the cubic phase at 768 K. These experimental results are supported by density functional theory calculations. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20